Use of supplements among the national track and field team members - Solaja, M.; Solaja, A.; Milankov, M. (3rd International Scientific Conference: Exercise and quality of life. April 12/13th 2013, 2013)
The standard diet of active athletes consist of various nutritional supplements. Today, the top results in track and field can not be achieved without the use of additives or supplements. The research included 78 athletes who are members of the junior and senior national team of Serbia (34 women and 44 men) aged 15 to 32 years. The research was conducted in the official training camp for the national selection in Bar (Montenegro), and research involved international respondents (N=37) and national (N=41) rank athletes.Data was collected by using a non-standardized survey research technique, questionnaire, andto determine the significance between the different variables was used nonparametric chi2 test. There were significant differences between men and women in the use of certain types of supplements. Also, there were significant differences in using the supplements among category level and track and field discipline.